BOX MEDIA MODEL THROUGH THE USE OF CONTEXTUAL UNDERSTANDING TO IMPROVE STUDENT LEARNING CONCEPTS IN VOLUME BEAM - Rohaeni, Dede (EDUTECH, 2016)
Abstract. This research is motivated Cilengkrang Elementary School fifth grade students in the learning of the beam volume is still experiencing difficulties. This happens because the learning process that takes place is conventional. Learning by applying a contextual model chosen researchers by reason students will know if the learning is associated with the real world of students. The method used in this research is a classroom action research methods to the design of the research procedure refers to the spiral model Kemmis and MC. Tujuanpenelitianini is to obtain an overview of the planning, implementation and improvement of students' understanding of the results of the application of the concept model of contextual learning in the classroom beam volume V Elementary School Cilengkrang. The method used in this research is a classroom action research methods to the design of the research procedure refers to the spiral model Kemmis and MC. Taggart. Based on the implementation of the actions performed by three cycles, as a whole has shown an increase from the initial data, both process and outcomes of learning. So that the application of contextual models can enhance students' understanding of class V SDN Cilengkrang Northern District of Sumedang Sumedang district of the concept of the beam volume. Keywords: Contextual Model, Mathematics, Mathematics Learning Objectives  Abstrak. Penelitian ini dilatarbelakangi siswa kelas V SDN Cilengkrang dalam pembelajaran volume balok masih mengalami kesulitan. Ini terjadi karena proses pembelajaran yang berlangsung bersifat konvensional. Pembelajaran dengan menerapkan model kontekstual dipilih peneliti dengan alasan siswa akan paham jika pembelajaran dikaitkan dengan dunia nyata siswa. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian tindakan kelas dengan rancangan prosedur penelitiannya mengacu pada model spiral Kemmis dan MC. Tujuanpenelitianini yaitu untuk memperoleh gambaran mengenai perencanaan, pelaksanaan dan peningkatan hasil pemahaman siswa dengan penerapan model kontekstual dalam pembelajaran konsep volume balok di kelas V SD Negeri Cilengkrang. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian tindakan kelas dengan rancangan prosedur penelitiannya mengacu pada model spiral Kemmis dan MC. Taggart. Berdasarkan pelaksanaan tindakan yang dilakukan sebanyak tiga siklus, secara keseluruhan telah menunjukan adanya peningkatan dari data awal, baik dalam proses maupun hasil belajar. Sehingga penerapan model kontekstual dapat meningkatkan pemahaman siswa kelas V SDN Cilengkrang Kecamatan Sumedang Utara Kabupaten Sumedang terhadap konsep volume balok. Kata Kunci: Model Kontekstual, Matematika, Tujuan Pembelajaran Matematika